2017
DOI: 10.1097/nmd.0000000000000682
|View full text |Cite
|
Sign up to set email alerts
|

Why We Need to Enhance Suicide Postvention

Abstract: Suicide prevention efforts are increasing to enhance capabilities and better understand risk factors and etiologies. Postvention, or how clinicians manage the postsuicide aftermath, strengthens suicide prevention, destigmatizes the tragedy, operationalizes the confusing aftermath, and promotes caregiver recovery. However, studies regarding its efficacy are minimal. The Psychopathology Committee of the Group for the Advancement for Psychiatry surveyed a convenience sample of psychiatrists to better understand p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…Some participants reported that they chose not to engage with support that was offered, despite feeling unsupported. Similar inconsistencies in accessing support even when it is available have been reported for those who are bereaved following suicide [ 49 , 50 ] and amongst practitioners [ 7 , 51 ]. This may in part be aligned with broader beliefs regarding mental health help-seeking.…”
Section: Discussionsupporting
confidence: 54%
“…Some participants reported that they chose not to engage with support that was offered, despite feeling unsupported. Similar inconsistencies in accessing support even when it is available have been reported for those who are bereaved following suicide [ 49 , 50 ] and amongst practitioners [ 7 , 51 ]. This may in part be aligned with broader beliefs regarding mental health help-seeking.…”
Section: Discussionsupporting
confidence: 54%
“…A study based on structured interviews of 20 therapists who had a patient suicide in their practice (29) found that 85% were much more direct in their assessment of suicidality after they had a suicide in their practice. Countertransference reactions described in the literature that can arise when continuing to work with suicidal patients include being overly protective and conservative in assessing risk, avoiding discussing suicidality, or avoiding patients at risk for suicide (2224, 30).…”
Section: Provider Experiencementioning
confidence: 99%
“…Indices were computed by summing item responses and dividing by the total number of items. Items created were consistent with previous research describing supports utilized by psychiatrists following patient suicide [ 22 ].…”
Section: Methodsmentioning
confidence: 99%